Pengaruh Financial Literacy dan Digital Payment (QRIS) Terhadap Kinerja Berkelanjutan UMKM Madura - Lailatul Fitriyah; Arie Setyo Purnomo; Prasetyo Nugroho (CV. Ulil Albab Corp, 2024)
MSMEs, as the main pillar of the Indonesian economy, have great potential to drive inclusive and sustainable economic growth. However, they face challenges, such as low financial literacy and lack of utilization of digital technology. This study analyzes the impact of financial literacy and adoption of digital payments (QRIS) on the sustainable performance of MSMEs in Pamekasan, Madura, using a causal quantitative method with purposive sampling and a 5-point Likert scale survey. The research procedure includes data instrument testing, classical assumption testing, and hypothesis testing. The results show that financial literacy and digital payments each have a significance value of 0.003 and 0.001, respectively, indicating a significant positive effect on MSME performance. Simultaneously, both also contribute significantly to the sustainable performance of MSMEs in Madura, with a significance value of F of 0.001. Business experience also plays an important role in the sustainability of MSMEs. The synergy between financial literacy, digital technology, and business experience creates conditions that support the sustainable performance of MSMEs, in line with the government's efforts to accelerate economic growth through creative MSME campaigns and encourage technology-based innovation.